DESAIN TERASERING PADA LERENG SUNGAI GAJAH PUTIH SURAKARTA - Dina Apriliana Purnamasari; Niken Silmi Surjandari; Sholihin As'ad (Program Studi Teknik Sipil FT UNS, 2014)
In one section of the slope of Gajah Putih river of Surakarta, slopes subjected to landslides due to not being able to withstand the river's water flowso that the battle occurred in the body of the land slope movement. The slope contained black clay deposit and this land were also converted to be aresidential. The factors generated land slide on that slope. Changing the slope geometry to more flater slope and formed as terrace is needed in orderto improve slope stability.The purpose of this research to know the safety factor value of slope on condition before repair and some variationcondition of terrace with ground water level use traffic load. Terrace various toward slope are 1/4H, 1/3H, 1/2H and H is height of slope. Theanalysis is done by manual calculation, using the simplified Bishop method.The results of the research are gotten safety factor value based on thefluctuation of ground water level and addition of dead load and dead load + life load on before terrace condition are smaller than after terracecondition. Therefore terrace construction increasing safety factor value. Ground water level position effect and load effect are dominant to influenceslope safety factor of Gajah Putih river. In this case, high of terrace position not too influence on this cases because the part which slide are less.